Detecting endometrial cancer. (27th February 2021) - Jones, Eleanor R; O'Flynn, Helena; Njoku, Kelechi; Crosbie, Emma J
Abstract : Key content: Endometrial cancer (EC) is the most common gynaecological cancer in the UK. Ninety percent of women with EC present with postmenopausal bleeding (PMB), but less than 10% of women with PMB have a sinister underlying cause. National Institute for Health and Care Excellence guidance advises that symptomatic postmenopausal women undergo urgent investigation; however, guidance is unclear for premenopausal women. Current investigations for PMB, including transvaginal ultrasound scan, endometrial biopsy and/or outpatient hysteroscopy, have advantages and disadvantages. Novel detection tools are in development, which combine minimally invasive sampling with genomic, proteomic and single cell technologies. Learning objectives: To understand who is at risk of EC and who should be referred for urgent investigations. To understand the evidence underpinning the current diagnostic pathway for EC. To highlight unique and promising perspectives for EC detection and their potential to transform clinical care. Ethical issues: Current diagnostics for EC are invasive and often painful. There is an urgent need for high‐quality randomised controlled trials to inform effective pain relief options. Premenopausal women with suspected EC do not fit criteria for urgent investigations. How can we identify those at highest risk to ensure they are fast‐tracked appropriately? Novel diagnostic tools hold promise, but they must be robustly validated before being introduced into clinical practice.